Agronomic Evaluation of Coffea ArAbica Variety Castillo and Caturra In Two Production Systems (Sun and Shade); In the Los Naranjos Farm, La Venta (Cajibio-Cauca) (Global Journal of Science Frontier Research, 2018)
Abstract not found
Keywords: coffee; production system; castle; caturra